PENGARUH TINGKAT PENDIDIKAN ORANG TUA DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS XI MATA PELAJARAN AKUNTANSI SMK NEGERI 1 KANDIS - Tymoti, Ibnu; Trisnawati, Fenny; Alia Sari, Filma (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
This study aims to determine the effect of parents' education level and learning motivation on the learning outcomes of class XI students of Accounting Subjects of SMK Negeri 1 Kandis. The type of research used is survey research with quantitative research methods. This research was conducted at SMK Negeri 1 Kandis with the total population in this study were 61 students, from class XI AKL 1 and AKL 2 with sampling techniques using a census. Data collection techniques were carried out by means of documentation to obtain student learning outcomes and questionnaires to obtain data on parents' education level and learning motivation. The collected data were then tabulated and analyzed using multiple linear regression with the help of SPSS version 27. The descriptive research results show that the level of parental education is in the middle category and learning motivation is in the high category while student learning outcomes are in the excellent category. The results of this study indicate that the level of parental education and learning motivation has a positive and significant effect on student learning outcomes with the regression equation Y = 79.121 + 1.472X1 + 0.177X2 + e and contributes to student learning outcomes by 39.7% and 60.3% is influenced by other variables not studied.